h^2 = a^2 + b^2
8^2 = 6^2 + x^2
64 = 36 + x^2
x^2 = 64 - 36
X^2 = 28
x = square root(28) = 5.29150262
2006-11-17 09:28:40
·
answer #1
·
answered by DanE 7
·
1⤊
1⤋
10
2006-11-17 09:54:43
·
answer #2
·
answered by drizzttownz 2
·
0⤊
1⤋
Using Pythagoras Theorem:
a^2 + b^2 = c^2
where a = ?
b = 6 cm
c = 8 cm
a^2 + 6^2 = 8^2
a^2 + 36 = 64
a^2 = 64 - 36
a^2 = 28
a = sq rt 28
a = 5.29 cm to 2 decimal places
2006-11-17 09:28:58
·
answer #3
·
answered by Loral 2
·
0⤊
0⤋
8cm=c, 6cm=b, ?=a
c^2 - b^2 = a^2
64 - 36 = the square root of 28
so, "a" can equal the square root of 28cm; or "a" can equal 5.291502622cm; or about 5.3cm. Pythagorean theorem
2006-11-17 09:43:50
·
answer #4
·
answered by honest abe 4
·
0⤊
0⤋
The teorem of Pythagora
a^2+b^2=c^2
. . . . . .
. . . . . . x
.. . . . x . x
..c . x . . x
. . .x . . . x. .a
. x. . . . . x
xxxxxxxxxx
. . . .b
so 6^2+b^2=8^2 =>
b^2=8^2-6^2=64-36=28 => b=sqrt(28)
==============================
2006-11-17 09:32:55
·
answer #5
·
answered by Broden 4
·
1⤊
0⤋
a^2+b^2=c^2 a^2+6^2=8^2 a^2=8^2-6^2 a^2=64-36 a^2=28 a=5.291
2006-11-17 14:21:24
·
answer #6
·
answered by sam 3
·
0⤊
0⤋
Square root of 28
2006-11-17 09:30:01
·
answer #7
·
answered by SMG 3
·
0⤊
1⤋
c squared = a squared + b squared
a squared = c squared -b squared
a= square root of 8 squared - 6 squared
a= square root of 64-36
a= square root of 28
a= 5.292 cm
2006-11-17 10:03:54
·
answer #8
·
answered by Max 6
·
0⤊
0⤋
a^2 + b^2 = c^2
a = x
c = 8
b = 6
x^2 + 6^2 = 8^2
x^2 = 8^2 - 6^2
x^2 = 64 - 36
x^2 = 28
x = 5.29
2006-11-17 09:31:51
·
answer #9
·
answered by johntadams3 5
·
0⤊
1⤋
10 cm.
2006-11-17 09:27:17
·
answer #10
·
answered by NONAME 7
·
0⤊
3⤋